Pengaruh Nilai Tukar Rupiah dan Suku Bunga terhadap Ekspor Ikan Indonesia ke Jepang - Apri, Apri Yola Ningsih; Sutrisno, Sutrisno; Abu, Ilham (Journal of Economic Education and Entrepreneurship Studies, 2024)
This study aims to determine the effect of the rupiah exchange rate and interest rates on Indonesian fish exports to Japan. The type of research used in this study is quantitative research.  The data collection technique used is documentation with the type of time series data for the last 11 years, namely from 2012-2022. The population and research sample are data on the rupiah exchange rate, interest rates and exports from 2012-2022. The data analysis techniques used are multiple linear regression equation tests, hypothesis testing and coefficient of determination analysis. The results showed that the rupiah exchange rate has a negative and significant effect on Indonesian fish exports to Japan. Meanwhile, interest rates have a positive and significant effect on Indonesian fish exports to Japan. Simultaneously, the rupiah exchange rate and interest rates together have a significant influence on Indonesian fish exports to Japan. The magnitude of the influence of the two independent variables on the dependent variable is about 96%.